2016
DOI: 10.1038/leu.2016.339
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of KLF4 promotes T-cell acute lymphoblastic leukemia and activates the MAP2K7 pathway

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy with a high incidence of relapse in pediatric ALL. Although most T-ALL patients exhibit activating mutations in NOTCH1, the cooperating genetic events required to accelerate the onset of leukemia and worsen disease progression are largely unknown. Here, we show that the gene encoding the transcription factor KLF4 is inactivated by DNA methylation in children with T-ALL. In mice, loss of KLF4 accelerated the development of NOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 60 publications
6
71
0
Order By: Relevance
“…We initially hypothesized that KLF4 may be inactivated in T-cell leukemogenesis because of its inhibitory role in the proliferation of T cells (16). Supporting this model, the analysis of multi-center international studies showed that KLF4 is significantly downregulated in pediatric T-ALL compared with normal bone marrow, particularly in more aggressive subtypes (ETP-ALL, TLX) associated with the worst prognosis (29). Alterations in DNA methylation are a hallmark of cancer and an important mechanism of gene silencing (30, 31).…”
Section: Emerging Role Of Klf4 In Hematological Malignanciesmentioning
confidence: 87%
See 4 more Smart Citations
“…We initially hypothesized that KLF4 may be inactivated in T-cell leukemogenesis because of its inhibitory role in the proliferation of T cells (16). Supporting this model, the analysis of multi-center international studies showed that KLF4 is significantly downregulated in pediatric T-ALL compared with normal bone marrow, particularly in more aggressive subtypes (ETP-ALL, TLX) associated with the worst prognosis (29). Alterations in DNA methylation are a hallmark of cancer and an important mechanism of gene silencing (30, 31).…”
Section: Emerging Role Of Klf4 In Hematological Malignanciesmentioning
confidence: 87%
“…Furthermore, the emerging paradigm is that epigenetic modifications can contribute to leukemogenesis and clonal heterogeneity in addition to recurring chromosomal aberrations and gene mutations (12, 32). Our analysis of promoter DNA methylation by targeted next-generation sequencing in a genomic region containing the proximal promoter and exons 1–2 of KLF4 revealed that most of the T-ALL patients displayed CpG hypermethylation—ranging from 10–20% to nearly 100%, particularly in the proximal promoter—in contrast to low or no methylation in normal bone marrow and T cells and patients with B-ALL (29). Supporting a correlation between KLF4 promoter methylation and gene expression, the treatment of T-ALL cell lines with 5-azacytidine (5-AZA) restored the expression of KLF4 and consequently inhibited cell proliferation and induced apoptosis.…”
Section: Emerging Role Of Klf4 In Hematological Malignanciesmentioning
confidence: 96%
See 3 more Smart Citations